2017
DOI: 10.1007/s10549-017-4355-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 21-gene recurrence score on outcome in patients with invasive lobular carcinoma of the breast

Abstract: For patients with ER-positive ILC, 8% were in the high-risk and 72% were in the intermediate-risk groups as per the TAILORx RS cutoffs. In the high-risk group, the RS predicted a lower 5-year BCSS. Adjuvant chemotherapy did not seem to confer a survival benefit for either the intermediate- or the high-risk cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 21 publications
4
55
0
1
Order By: Relevance
“…14,15 In fact, recent data has suggested that ORS may be less useful in predicting response to adjuvant chemotherapy in patients with invasive lobular carcinoma. 16 These data raise the question whether ORS should be interpreted with caution in invasive carcinomas with favorable histology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15 In fact, recent data has suggested that ORS may be less useful in predicting response to adjuvant chemotherapy in patients with invasive lobular carcinoma. 16 These data raise the question whether ORS should be interpreted with caution in invasive carcinomas with favorable histology.…”
Section: Discussionmentioning
confidence: 99%
“…There are several multigene assays used to predict the risk of distant recurrence and the potential benefit of systemic therapy in lymph node-negative, estrogen receptor positive, human epidermal growth factor receptor-2 (HER2)-negative invasive carcinomas. 1 Oncotype Dx ® measures the expression of 21 genes to calculate a quantitative recurrence score (ORS) that is stratified into 3 categories: low risk (0-10), intermediate risk (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), and high risk (≥26) based on the prospective TAILORx trial. 2 Oncotype Dx ® has been incorporated into the AJCC 2017 staging criteria for estrogen receptor positive, HER2-negative, and lymph node-negative invasive carcinomas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lobular BC was associated with low and intermediate RS (P < .001) ( Table 2). Low RS (range, 0-11), intermediate RS (range, [12][13][14][15][16][17][18][19][20][21][22][23][24][25], and high RS (range, 26-100) Oncotype DX categories were observed in 20%, 72%, and 8% lobular BCs, respectively. The prevalence of high RS results was 3-fold lower in lobular BC compared with nonlobular BC (8% vs 24%; P < .001).…”
Section: Lower Rs In Lobular Bcmentioning
confidence: 98%
“…It is probable that applying a selective pressure such as chemotherapy could cause the emergence of treatment-resistant clones [43]. As the use of chemotherapy is disputed for lobular breast cancer [44], sub-analyses of women with lobular breast cancer was performed. The data showed wide confidence intervals, indicating limit power and therefore no meaningful conclusions could be drawn.…”
Section: Discussionmentioning
confidence: 99%